On The Influence of The Phonetic Laws of The Uzbek Language in The Teaching of German (Journal of Pedagogical Inventions and Practices, 2021)
In order for a language learner to pronounce correctly, he or she must know the accents, rhythm, tone, which affects the content. The specific features of the German phonetic system are: Each vowel letter is represented by 4 different sounds, i.e. 6 vowel letters give 20 sounds or are pronounced; More than one letter of sound: 26 letters correspond to more than 30 sounds; the presence of diphthongs; [ai] [ao]